The role of solid bone marrow aspirate concentrate in enhancing gingival wound repair in rabbits - A. L. Alshibib (Regulatory Mechanisms in Biosystems, 2025)
Healing of wounds involves factors such as inflammation and the formation of new tissue in the body ’ s healing process. In this research project on the healing process of gingival wounds in rabbits using s olid b one m arrow a spirate concentrate ( s BMAC) , twelve male New Zealand White rabbits were split into two groups , o ne receiving saline treatment and the other treated with s BMAC. Histological and immunohistochemical examinations were conducted at two time points; three days and seven days after the surgery to evaluate the presence of inflammation and granulation tissue formation well as to observe angiogenesis and epithelialization processes. The findings indicate that sBMAC notably improved the stages of healing processes. On the 3 rd day of observation wounds treated with sBMAC showed advancements in the formation of granulation tissue, angiogenesis and reepithelialization compared to the control group. By the 7 th day both groups demonstrated progress in wound healing . H owever the sBMAC treated group exhibited structured granulation tissue, superior tissue maturity and heightened epithelial regeneration. The inflammatory response was also considerably reduced in the sBMAC group by Day 7 , which suggests ma n agement of inflammation. The examination using immunohistochemistry showed levels of pan cytokeratin and TGF-β in the group treated with sBMAC , which indicates its effectiveness in stimulating the growth of cells and tissues.This discovery implies that sBMAC aids in speeding up the stages of wound healing and plays a part in improving tissue regeneration methods, for better soft tissue repair outcomes.